Single-double-layer assembled flame-retardant and smoke-suppressing polyester fabric and preparation method thereof

By using single-time double-layer assembly technology of gelatin and montmorillonite on the surface of polyester fabrics, an efficient flame retardant and smoke suppression coating was constructed, which solved the complex flame retardant modification process of polyester fabrics and the difficulty in improving smoke release problems, and achieved efficient and environmentally friendly flame retardant and smoke suppression effect.

CN116219751BActive Publication Date: 2025-04-29JIANGNAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211672225.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-04-29
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

The flame retardant modification of polyester fabrics requires a complex finishing process. The self-assembly technology requires a wide range of assembly layers, cumbersome processes, and the smoke release problem during combustion is difficult to improve.

Method used

The solution of montmorillonite in a homogeneous dispersed nanoparticle montmorillonite is used as anionic solution, and the polyelectrolyte complex solution formed by gelatin and phytic acid is used as a cationic solution. A high-efficiency flame retardant and smoke-resisting coating is constructed on the surface of polyester fabrics through single double-layer assembly.

Benefits of technology

It achieves the ideal flame retardant and smoke suppression effect in a single assembly, with the limit oxygen index up to 32.4, and the smoke release can be reduced by up to 64%, avoiding high-energy radiation and high-temperature baking, and the process is gentle and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116219751B_ABST
    Figure CN116219751B_ABST
Patent Text Reader

Abstract

The invention discloses a single-double-layer assembled flame-retardant smoke-suppressing polyester fabric and a preparation method thereof, and belongs to the technical field of flame-retardant finishing of textiles. The invention adopts a macromolecular gelatin-uniformly dispersed nanoparticle montmorillonite solution as an anion solution, and a polyelectrolyte complex solution formed by gelatin and phytic acid as a cationic solution. The assembly is efficient and simple, the conditions are mild, and it is green and environmentally friendly. The flame-retardant fabric can be obtained by a single assembly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a single-double-layer assembled flame-retardant and smoke-suppressing polyester fabric and a preparation method thereof, belonging to the technical field of flame-retardant finishing of textiles. Background Art

[0002] The growing demand for textiles, especially polyester fabrics, and the increasing awareness of fire safety have greatly promoted the development of highly efficient flame-retardant textiles. An important way to achieve this goal is to use a large amount of phosphorus-nitrogen flame retardants, which show good synergistic effects in suppressing, mitigating and eliminating fire hazards. In recent years, new processing technologies such as radiation grafting and layer-by-layer self-assembly have been increasingly used in the modification and processing of textiles. Compared with other technologies, the layer-by-layer self-assembly technology has mild conditions and high controllability. It can adsorb different molecules through a variety of forces to give the fabric different properties.

[0003] However, the layer-by-layer self-assembly technology also has certain limitations and disadvantages. The application of layer-by-layer self-assembly is usually accompanied by multi-layer deposition, and the multi-step adsorption process makes this technology subject to many restrictions in practical applications. In addition, the alternating deposition of anions and cations is highly dependent on the ionic strength and pH value of the two groups of solutions. The use of acid and alkaline solutions will increase the complexity of using such technology. Developing a simpler and less-layered flame-retardant coating is an urgent problem that needs to be solved by the current layer-by-layer self-assembly technology.

[0004] CN105951419B provides a polyester fiber modified with a cross-linked layer-by-layer self-assembled flame-retardant coating and a preparation method thereof, wherein phosphazene compounds or chitosan are used as positive electrolytes, and subnitrile compounds containing a DOPO structure, subnitrile compounds containing a phosphate ester structure, or sodium alginate are used as negative electrolytes, and the pre-treated polyester fiber is alternately immersed in positive and negative electrolyte solutions, and then immersed in a catalyst solution, so that the positive and negative electrolyte coatings are cross-linked to obtain flame-retardant polyester fibers. The polyester fiber obtained by this method after optimizing the pH value has excellent flame retardancy, and the required assembled coating is 20-30 layers.

[0005] CN109183408B provides a layer-by-layer self-assembled flame-retardant cotton fabric and a preparation method thereof, wherein phytic acid and a self-made nitrogen-containing compound PCQS are used as anion and cation components, respectively, and a flame-retardant coating is formed by alternately depositing them on the surface of the cotton fabric. This method can easily combine the self-made effective components with the existing flame-retardant components to construct a new flame-retardant coating, but in this invention, the pH value required for the solution when the anions and cations are optimally deposited needs to be explored, and the number of deposition layers required when the limiting oxygen index of the flame-retardant cotton fabric reaches 29.8 is 30 layers.

[0006] CN105755836B provides a three-component layer-by-layer self-assembled flame-retardant modified ramie fabric and a preparation method thereof, wherein polyethyleneimine solution / zirconium phosphate solution and polyethyleneimine solution / ammonium polyphosphate solution are used as two groups of anion and cation solutions, and ramie fabric is sequentially immersed in the first group and the second group of anion and cation solutions to obtain a flame-retardant ramie fabric. The number of layers immersed in the first group of anion and cation solutions is 5-10, and the number of layers immersed in the second group of anion and cation solutions is 0-5. Summary of the invention

[0007]

Technical issues

[0008] At present, the flame retardant modification of polyester fabrics requires a complex finishing process. When using layer-by-layer self-assembly technology, a large number of assembly layers are required to achieve the ideal effect, the process is cumbersome, and the smoke release problem of polyester fabrics when burning is difficult to improve.

[0009]

Technical solution

[0010] In view of the above problems existing in the prior art, the present invention provides a method for constructing an efficient flame retardant and smoke suppression coating on the surface of polyester fabric by a single double-layer assembly. The present invention uses a macromolecular gelatin-uniformly dispersed nanoparticle montmorillonite solution as an anion solution, and a polyelectrolyte complex solution formed by gelatin and phytic acid as a cationic solution. The assembly is efficient and simple, the conditions are mild, and it is green and environmentally friendly. A flame retardant fabric can be produced by a single assembly. The present invention only requires one layer to make the substrate achieve the ideal flame retardant and smoke suppression effect, where one layer refers to one alternating deposition of anion and cation solutions.

[0011] The first object of the present invention is to provide a flame retardant finishing agent, which is divided into liquid A and liquid B; liquid A includes gelatin and montmorillonite, and liquid B includes gelatin and a compound containing a phosphoric acid or phosphorous acid group.

[0012] In one embodiment of the present invention, the concentration ratio of gelatin to montmorillonite in liquid A is 1:1-1:2; the concentration of gelatin is 1-2wt%, and the concentration of montmorillonite is 2-4wt%.

[0013] In one embodiment of the present invention, the compound containing a phosphate or phosphite group comprises phytic acid or phosphoric acid.

[0014] In one embodiment of the present invention, the concentration ratio of gelatin to the compound containing phosphoric acid or phosphorous acid groups in liquid B is 1:1-1:4; the concentration of gelatin is 2-4wt%, and the concentration of phytic acid is 4-8wt%.

[0015] The second object of the present invention is to provide a use of the flame retardant finishing agent in preparing flame retardant materials.

[0016] The third object of the present invention is to provide a method for flame retardant finishing of fabrics, wherein the fabrics are treated with an adhesive spreading liquid and then the flame retardant finishing agent is used to perform flame retardant finishing on the fabrics.

[0017] In one embodiment of the present invention, the concentration of the polyethyleneimine solution in the adhesive spreading liquid is 1-2 wt %.

[0018] In one embodiment of the present invention, the flame retardant finishing is to treat the fabric in the order of adhesive spreading liquid, A liquid and B liquid.

[0019] In one embodiment of the present invention, the type of fabric is not limited, including woven fabrics, knitted fabrics and non-woven materials, and the type of fabric fiber is also not limited, including cotton, wool, silk, linen, polyester, viscose, nylon and other fabrics, and is not limited to fabrics, including substrates such as polyurethane foam, wood, and aerogel.

[0020] In one embodiment of the present invention, the fabric finishing conditions are: the bath ratio of the fabric to the adhesive spreading liquid is 1: (20-80), and the treatment time is 1-30 min; the bath ratio of the fabric to liquid A is 1: (50-100), and the treatment time is 1-30 min; the bath ratio of the fabric to liquid B is 1: (50-100), and the treatment time is 1-30 min.

[0021] In one embodiment of the present invention, the preparation method of the flame retardant and smoke suppressing polyester fabric is as follows:

[0022] (1) Preparation of alkali treatment solution and alkali treatment of polyester fabric

[0023] Dissolve sodium hydroxide in deionized water and stir to prepare an alkali treatment solution. Immerse the polyester fabric in the solution and treat it at 50-80°C for 30-90 minutes, then wash and dry for later use.

[0024] (2) Preparation of base layer adhesive spreading liquid

[0025] Dissolve the branched polyethyleneimine in deionized water to prepare the base layer adhesive spreading solution. The polyethyleneimine can form a layer of positive charge on the surface of the fabric, while reducing the surface tension of the subsequent solution on the surface of the fabric, which is conducive to the uniform adsorption of the flame retardant coating.

[0026] (3) Preparation of anionic solution

[0027] Dissolve gelatin and montmorillonite in deionized water, mix and stir after fully dissolving to obtain an anionic solution. Gelatin provides an expansion source in the flame retardant coating on the one hand, and on the other hand, it can form a natural shell "brick-mud" bionic structure with montmorillonite to introduce nanoparticles into the fabric coating; montmorillonite, as a ceramic precursor, promotes the formation of a ceramic carbon layer when the substrate is heated.

[0028] (4) Preparation of cationic solution

[0029] Dissolve gelatin in deionized water, add phytic acid after it is fully dissolved, stir, and prepare a cationic solution. Gelatin provides a swelling source in the flame retardant coating on the one hand, and forms a polyelectrolyte complex solution with phytic acid on the other hand, serving as a binding link in the anion-cation solution to enhance the anion-cation interface binding force; phytic acid can provide an acid source in the flame retardant coating.

[0030] (5) Preparation of flame-retardant and smoke-suppressing polyester fabrics

[0031] The polyester fabric prepared in step (1) is sequentially immersed in the solutions prepared in steps (2), (3) and (4), and the polyester fabric is fully dried after each immersion in the solution.

[0032] In one embodiment of the present invention, the concentration of sodium hydroxide in step (1) is 2-4 wt %.

[0033] In one embodiment of the present invention, the concentration of the base layer adhesive spreading liquid in step (2) is 1-2 wt %.

[0034] In one embodiment of the present invention, in the anion solution described in step (3), the concentration of gelatin is 1-2 wt %, and the concentration of montmorillonite is 2-4 wt %.

[0035] In one embodiment of the present invention, in the cationic solution described in step (4), the concentration of gelatin is 2-4 wt %, and the concentration of phytic acid is 4-8 wt %.

[0036] In one embodiment of the present invention, the anion and cation solutions described in steps (3) and (4) do not need to be further regulated in pH value.

[0037] In one embodiment of the present invention, the immersion time of the fabric in each solution in step (5) is 1-30 minutes.

[0038] The fourth object of the present invention is to provide a flame retardant fabric prepared by the above method.

[0039] A fifth object of the present invention is to provide a product containing the flame retardant fabric.

[0040] Beneficial effects of the present invention:

[0041] (1) The gelatin, montmorillonite and phytic acid used in the present invention are all green chemicals, environmentally friendly, widely available and low in cost.

[0042] (2) Different from the radiation grafting and rolling baking finishing methods commonly used for polyester fabric modification, the present invention adopts layer-by-layer self-assembly technology to deposit the flame retardant onto the surface of the polyester fabric, avoiding high-energy radiation and high-temperature baking, making the finishing conditions milder, and eliminating the need to add chemical additives such as initiators and adhesives, thus saving energy.

[0043] (3) The present invention combines the dispersion technology of nanoparticles in macromolecules with the polyelectrolyte strategy, and only one layer is required to achieve a maximum weight gain of 44.7% using a small amount of flame retardant, thus overcoming the technical difficulty of the current layer-by-layer self-assembly technology that requires repeated deposition of multiple layers.

[0044] (4) The present invention ingeniously constructs an organic-inorganic hybrid flame-retardant coating on the surface of polyester fabric. The limiting oxygen index of the prepared finished polyester fabric can reach up to 32.4. When encountering an external fire source, the total amount of smoke released can be reduced by up to 64%. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 These are horizontal flame spread test diagrams for original polyester and Examples 1, 2, and 3. DETAILED DESCRIPTION

[0046] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0047] Test Method

[0048] Limiting oxygen index test: According to GB / T 5454-1997 "Textile combustion performance test oxygen index method", cut the flame retardant polyester fabric into at least 5 pieces, the sample size is about 25×6cm 2 In the oxygen-nitrogen mixed gas flow, the minimum oxygen concentration required to maintain its combustion is expressed as a percentage.

[0049] Horizontal flame spread test: According to ASTM D 4986, during the test, the sample (100*50mm 2 ) is placed in a metal frame and tilted 45 degrees in the direction of its long axis, and then the short side is ignited for 6 seconds with a 40 mm methane flame. The burning time, combustion performance and other parameters are recorded during the test. Each sample is tested at least three times.

[0050] Smoke release test: According to ISO 5660 standard, each sample was cut into a 100×100 mm square and tested at 50 kW / m 2 The radiant heat flux is placed horizontally. The combustion behavior of the sample is studied. Each sample is tested at least 3 times.

[0051] Embodiment 1:

[0052] (1) Preparation of alkali treatment solution and alkali treatment of polyester fabric

[0053] Sodium hydroxide was dissolved in deionized water and stirred to prepare a 2 wt% alkali treatment solution. Polyester fabric was immersed in the solution and treated at 60°C for 60 minutes, then washed and dried for later use.

[0054] (2) Preparation of base layer adhesive spreading liquid

[0055] The branched polyethyleneimine was dissolved in deionized water to prepare a base layer adhesive spreading solution with a concentration of 1 wt%.

[0056] (3) Preparation of anionic solution

[0057] Gelatin and montmorillonite are dissolved in deionized water, and after being fully dissolved, they are mixed and stirred to prepare an anionic solution, wherein the gelatin concentration is 1 wt % and the montmorillonite concentration is 2 wt %.

[0058] (4) Preparation of cationic solution

[0059] Gelatin was dissolved in deionized water. After fully dissolved, phytic acid was added and stirred to prepare a cationic solution, wherein the gelatin concentration was 2 wt % and the phytic acid concentration was 4 wt %.

[0060] (5) Preparation of flame-retardant and smoke-suppressing polyester fabrics

[0061] The polyester fabric prepared in step (1) is sequentially immersed in the solutions prepared in steps (2), (3) and (4), and the polyester fabric is fully dried after each immersion in the solution.

[0062] Example 2

[0063] (1) Preparation of alkali treatment solution and alkali treatment of polyester fabric

[0064] Sodium hydroxide was dissolved in deionized water and stirred to prepare a 2 wt% alkali treatment solution. Polyester fabric was immersed in the solution and treated at 60°C for 60 minutes, then washed and dried for later use.

[0065] (2) Preparation of base layer adhesive spreading liquid

[0066] The branched polyethyleneimine was dissolved in deionized water to prepare a base layer adhesive spreading solution with a concentration of 1 wt%.

[0067] (3) Preparation of anionic solution

[0068] Gelatin and montmorillonite were dissolved in deionized water, and after being fully dissolved, they were mixed and stirred to prepare an anionic solution, wherein the gelatin concentration was 1.5 wt % and the montmorillonite concentration was 3 wt %.

[0069] (4) Preparation of cationic solution

[0070] Gelatin was dissolved in deionized water. After fully dissolved, phytic acid was added and stirred to prepare a cationic solution, wherein the gelatin concentration was 3 wt % and the phytic acid concentration was 6 wt %.

[0071] (5) Preparation of flame-retardant and smoke-suppressing polyester fabrics

[0072] The polyester fabric prepared in step (1) is sequentially immersed in the solutions prepared in steps (2), (3) and (4), and the polyester fabric is fully dried after each immersion in the solution.

[0073] Example 3

[0074] (1) Preparation of alkali treatment solution and alkali treatment of polyester fabric

[0075] Sodium hydroxide was dissolved in deionized water and stirred to prepare a 2 wt% alkali treatment solution. Polyester fabric was immersed in the solution and treated at 60°C for 60 minutes, then washed and dried for later use.

[0076] (2) Preparation of base layer adhesive spreading liquid

[0077] The branched polyethyleneimine was dissolved in deionized water to prepare a base layer adhesive spreading solution with a concentration of 1 wt%.

[0078] (3) Preparation of anionic solution

[0079] Gelatin and montmorillonite were dissolved in deionized water, and after being fully dissolved, they were mixed and stirred to prepare an anionic solution, wherein the gelatin concentration was 2 wt % and the montmorillonite concentration was 4 wt %.

[0080] (4) Preparation of cationic solution

[0081] Gelatin was dissolved in deionized water. After fully dissolved, phytic acid was added and stirred to prepare a cationic solution, wherein the concentration of gelatin was 4 wt % and the concentration of phytic acid was 8 wt %.

[0082] (5) Preparation of flame-retardant and smoke-suppressing polyester fabrics

[0083] The polyester fabric prepared in step (1) is sequentially immersed in the solutions prepared in steps (2), (3) and (4), and the polyester fabric is fully dried after each immersion in the solution.

[0084] Example 4

[0085] The flame retardant polyurethane foam was prepared by referring to the method of Example 3, except that the polyester fabric was replaced with polyurethane foam, and other conditions remained unchanged.

[0086] Embodiment 5:

[0087] The method of Example 3 was used with reference to that of Example 3, except that the amount of montmorillonite added was adjusted to 2 wt %, and other conditions remained unchanged.

[0088] After many tests, it was found that when the ratio of gelatin and montmorillonite in the anion solution is controlled within the range of 1:1-1:2, a better flame retardant effect can be achieved. Exceeding this range will cause the anion solution to be unstable, the interfacial polymerization force of the anion and cation layers to be reduced, and the flame retardant and smoke suppression effect of the assembled polyester fabric to be unsatisfactory.

[0089] Embodiment 6:

[0090] The method of Example 3 is referred to, except that phytic acid is replaced by phosphoric acid, and other conditions remain unchanged.

[0091] After many tests, it was found that substances containing phosphoric acid or phosphorous acid groups can achieve such an effect in this flame retardant and smoke suppression coating.

[0092] Comparative Example 1:

[0093] The method of Example 3 is referred to, except that the gelatin in the anion and cation solution is omitted, and other conditions remain unchanged.

[0094] Comparative Example 2:

[0095] Steps (3) and (4) of Example 1 are adjusted: (3) preparing a mixed anion and cation solution: mixing the anion and cation solutions to obtain a mixed solution, wherein the gelatin concentration of the mixed solution is 1wt%, the montmorillonite concentration is 2wt%, and the phytic acid concentration is 4wt%.; (4) preparing a flame-retardant and smoke-suppressing polyester fabric: immersing the polyester fabric obtained in step (1) in the solutions obtained in steps (2) and (3) in sequence, and the polyester fabric is fully dried after each immersion in the solution. The other steps are the same as those of Example 1.

[0096] The obtained flame retardant material was subjected to performance tests, and the test results are as follows:

[0097] Table 1

[0098]

[0099]

[0100] The results are shown in Table 1. It can be seen from Table 1 that the flame retardant coating constructed by the present invention has excellent flame retardant improvement, anti-melting dripping effect and smoke suppression effect on polyester fabrics. No melting dripping phenomenon was observed on the finished polyester fabric during combustion, and its limiting oxygen index can reach up to 32.4, and the smoke release can be reduced by up to 63.6%, which can effectively slow down the spread of flame. In addition, when the invented coating is applied to polyurethane foam, the prepared flame retardant foam also shows satisfactory flame retardant and smoke suppression effects. It can be seen that the invented flame retardant and smoke suppression coating is not limited to polyester fabrics. Changes, deletions or replacements of the amount of raw materials in the coating constructed by the present invention with other materials will affect the flame retardant and smoke suppression properties of the flame retardant polyester fabric.

[0101] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A smoke suppression and anti-drip flame retardant finishing agent, characterized in that: The smoke-suppressing and anti-drip flame-retardant finishing agent is divided into liquid A and liquid B; liquid A includes gelatin and montmorillonite, and liquid B includes gelatin and a compound containing a phosphate or phosphite group, and the compound containing a phosphate or phosphite group includes phytic acid or phosphoric acid; the concentration ratio of gelatin to montmorillonite in liquid A is 1:1-1:2; the concentration of gelatin is 1-2 wt%, and the concentration of montmorillonite is 2-4 wt%; the concentration ratio of gelatin to the compound containing a phosphate or phosphite group in liquid B is 1:1-1:4; the concentration of gelatin is 2-4 wt%, and the concentration of the compound containing a phosphate or phosphite group is 4-8 wt%.

2. Use of the smoke-suppressing and anti-drip flame-retardant finishing agent according to claim 1 in the preparation of flame-retardant materials.

3. A method for smoke suppression and anti-drip flame retardant finishing of fabrics, characterized in that: The method comprises treating the fabric with an adhesive spreading liquid, and then performing flame retardant finishing on the fabric using the smoke-suppressing and anti-drip flame retardant finishing agent of claim 1. The method comprises treating the fabric in the order of the adhesive spreading liquid, liquid A, and liquid B.

4. The method according to claim 3, characterized in that The concentration of the polyethyleneimine solution in the adhesive spreading solution is 1-2 wt%.

5. The method according to claim 3 or 4, characterized in that The fabric finishing conditions are as follows: the bath ratio of fabric to adhesive spreading liquid is 1: (20-80), and the treatment time is 1-30 min; the bath ratio of fabric to liquid A is 1: (50-100), and the treatment time is 1-30 min; the bath ratio of fabric to liquid B is 1: (50-100), and the treatment time is 1-30 min.

6. A flame retardant fabric prepared by the method according to any one of claims 3 to 5.

7. An article comprising the flame retardant fabric according to claim 6.

Citation Information

Patent Citations

  • A three-component layer-by-layer self-assembled flame-retardant modified ramie fabric and its preparation method

    CN105755836B

  • Polyester fiber modified with cross-linked layer-by-layer self-assembled flame-retardant coating and preparation method thereof

    CN105951419B

  • A layer-by-layer self-assembled flame-retardant cotton fabric and its preparation method

    CN109183408B

  • Device and method for alternately applying finishing agents to textiles

    CN110004619A

  • Metal-doped polyelectrolyte coating liquid, coating, flame-retardant material and preparation thereof

    CN114108332A